PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. VALBURY ASIA FUTURES (VAF) KUNINGAN JAKARTA SELATAN - M. Megi Zakaria; Retno Japanis Permatasari (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of motivation on employee performance at PT. Valbury Asia Futures (VAF) Kuningan, South Jakarta. To determine the effect of work discipline on employee performance at PT. Valbury Asia Futures (VAF) Kuningan, South Jakarta. To determine the influence of motivation and work environment on employee performance at PT. Valbury Asia Futures (VAF) Kuningan, South Jakarta. This type of research is quantitative. The data analysis techniques used in this research are instrument testing, classical assumption testing, regression testing, correlation coefficient testing, coefficient of determination testing and hypothesis testing. The population in this study were employees at PT. Valbury Asia Futures (VAF) had 73 employees and the sample used was 73 respondents. The results of the research show that motivation has a positive and significant effect on employee performance, this is proven by the tcount > ttable (8.002 > 1.994) and the sig value < 0.05 (0.000 < 0.05) so that H0 is rejected and H1 is accepted, there is a positive influence and significant relationship between motivation and employee performance. Work Discipline has a positive and significant effect on employee performance, this is proven by the value of t count > t table (5.229 > 1.994) and the sig value < 0.05 (0.000 < 0.05) so that H0 is rejected and H2 is accepted, there is a positive and significant influence between work discipline on employee performance. Motivation and Work Discipline have a positive and significant effect on employee performance, this is proven by F count > F table (35.100 > 3.13) and sig value < 0.05 (0.000 < 0.05), there is a positive and significant influence between motivation and work discipline simultaneously on employee performance. The coefficient of determination R Square of 0.501 states that the variables motivation (X1) and work discipline (X2) have a contribution of 50.1% to employee performance (Y) and the remaining 49.9% influences other factors.